2007
DOI: 10.3354/meps335271
|View full text |Cite
|
Sign up to set email alerts
|

Fisheries-induced evolution: present status and future directions

Abstract: This essay comments on recent research on Darwinian fisheries science and on the future development of this field. From a practical point of view, the key question is: how fast are evolutionary changes caused by fishing happening? To answer this question, there is a need to understand intensities of selection generated by fishing, heritabilities and genetic correlations of the traits under selection, and whether the rates of change in traits predicted from this information are consistent with the changes obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
323
2
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 267 publications
(333 citation statements)
references
References 46 publications
6
323
2
2
Order By: Relevance
“…Fish that mature at smaller sizes have lower reproductive output, but they also avoid growing into vulnerable size classes where their survival would be low. In contrast to trap nets, gill nets present two size refuges for fish, and the presence of an upper size refuge has the potential to buffer a population from the long‐term evolutionary effects of fishing (Jørgensen et al., 2009; Law, 2007). However, this was not an outcome for Lake Huron lake whitefish when fishing with 114‐mm gill nets, the mesh size currently dominating in the commercial fishery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fish that mature at smaller sizes have lower reproductive output, but they also avoid growing into vulnerable size classes where their survival would be low. In contrast to trap nets, gill nets present two size refuges for fish, and the presence of an upper size refuge has the potential to buffer a population from the long‐term evolutionary effects of fishing (Jørgensen et al., 2009; Law, 2007). However, this was not an outcome for Lake Huron lake whitefish when fishing with 114‐mm gill nets, the mesh size currently dominating in the commercial fishery.…”
Section: Discussionmentioning
confidence: 99%
“…A frequent recommendation is to protect large fecund fish, which could be done, for example, by fishing using a gear type with bell‐shaped size selectivity (Hixon et al., 2014; Law, 2007). Small mesh gill nets in particular can favor delayed maturation, extend the age and size distribution of the population, and result in good fisheries yield in the long term (Jørgensen et al., 2009; Zimmerman & Jørgensen, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, selection experiments enable concentrating attention on traits of interest for fisheries. Prime examples are maturation traits, which are particularly susceptible to FIE (Audzijonyte et al 2013, Dunlop et al 2009) and have been observed to change in response to fishing pressure after accounting for major sources of plasticity (Heino & Dieckmann 2008, Law 2007. Selection experiments also allow assessing the rate at which changes happen, their reversibility, and their effect on population productivity and fishery profitability, which are major issues for resource management.…”
Section: Experimental Evidencementioning
confidence: 99%
“…Those that that are genetically predisposed to mature earlier then have a selective advantage under fishing pressure and a greater chance of contributing spawning products over late-maturing individuals. This ultimately leads to directional selection for early maturing females in the population (Rijnsdorp 1993;Kraak 2007;Law 2007 and papers in theme session entitled Disentangling the causes of maturation trends in exploited fish populations, Mar Ecol Prog Ser. 335 (2007)).…”
Section: Fishing and Its Effect On Productionmentioning
confidence: 99%